Effect of NaClO disinfection/cleaning on passive films on AISI 316L. (1st April 2020) - Tranchida, G.; Di Franco, F.; Virtanen, S.; Santamaria, M.
Highlights: 316 L stainless steel samples were passivated in NaClO disinfection solution. Passive films were characterized by Photocurrent Spectroscopy, XPS and EIS measurements. Passivation kinetic was studied as function of chlorine concentration, time and temperature. Abstract: 316 L stainless steel samples were passivated in NaClO containing solutions in order to simulate disinfection processes. Passive films were grown at the open circuit potential by immersion in NaClO aqueous solutions at different concentrations and temperature in order to understand how exposure to aggressive environments could affect subsequent corrosion resistance of SSs. In the attempt to study the passive film growth mechanism, in-situ Open Circuit Potential measurements were performed in the same growth solutions. Photoelectrochemical and impedance investigation of passive films was carried out in order to link their solid state properties with their corrosion behaviour.